2010
DOI: 10.1136/jmg.2010.080366
|View full text |Cite
|
Sign up to set email alerts
|

Salbutamol increases survival motor neuron (SMN) transcript levels in leucocytes of spinal muscular atrophy (SMA) patients: relevance for clinical trial design

Abstract: The data strongly support salbutamol as a candidate for treating SMA, and suggest that SMN2 copy number may predict the molecular response to treatment and may be a useful randomisation parameter in a double blind placebo controlled clinical trial design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 11 publications
3
44
0
2
Order By: Relevance
“…Some therapeutic approaches aim to increase the amount of SMN protein produced by SMN2 through promoter activation, reduction of exon 7 alternative splicing, or both. [13][14][15][16][17][18][19][20][21][22] Some of these approaches are being investigated in ongoing or planned clinical trials, and great efforts have been done to identify the most appropriate clinical outcome measures for patients affected from various severities. 23 In this view, it would be very useful to have reliable biomarkers of disease severity and response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Some therapeutic approaches aim to increase the amount of SMN protein produced by SMN2 through promoter activation, reduction of exon 7 alternative splicing, or both. [13][14][15][16][17][18][19][20][21][22] Some of these approaches are being investigated in ongoing or planned clinical trials, and great efforts have been done to identify the most appropriate clinical outcome measures for patients affected from various severities. 23 In this view, it would be very useful to have reliable biomarkers of disease severity and response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The different technical approaches utilized are analyzed in detail throughout this section. [121][122][123][124][125][126][127] A greater number of studies belong to the second category, as the majority of therapeutic approaches have aimed to increase SMN protein levels by increasing the level of SMN transcripts. An exception to this transcript ''rule'' is the modification of SMN protein stability, 117 where a change in SMN transcript levels is not expected.…”
Section: Smn Transcript Assaysmentioning
confidence: 99%
“…In another open trial on 23 SMA type II patients, the functional scores were significantly higher after 6 and 12 months of treatment with salbutamol and there were no major side effects [116]. Tiziano et al [117] reported that oral administration of salbutamol (albuterol) for 6 months, [7]. Some interesting and promising data show that these stem cell-derived motor neurons can grow axons and form neuromuscular junctions in preclinical experiments [123,124].…”
Section: Thyrotropin Releasing Hormone (Trh) Hasmentioning
confidence: 99%